AN ANALYSIS OF DIFFICULTIES IN WRITING ESSAY AT SECOND GRADE OF EDUCATION COLLEGE OF STKIP - Irsyad Nugraha (English Education and Applied Linguistics Journal (EEAL Journal), 2019)
Writing as one of the four skills in English has an important role for undergraduate students. This is because writing is productive skill which can build and rebuild the student’s motivation in mastering language. Writing is a basic skill for students, because it can improve students’ abilities in mastering language. In the process, writing skills has so many problems and solutions to enrich student’s capabilities. Population for this research is one purposed random sampling of second grade English Department students. The writer tries to get the sample only 20 students, which were taken from 90 students of second grade populations furthermore the writer tries to choose students with high cumulative mark and low cumulative mark to get the varieties problems of Essay Writing. The writer obtained the instrument of data by using some questionnaires and interview for students in order to analyze wh